Public Theology: An Ever-Changing Task. Issue 2 (8th November 2016) - Miller, Vincent J.
Abstract : Public theology involves political and rhetorical engagement in political debates about the social consequences of Christian commitment, and prudential attempts to judge and form public debate with Christian theological and moral principles. It has consequences for our understanding of Christian discipleship as much as it does for public debate.